THE INFLUENCE OF TAX MORALS, TAX KNOWLEDGE AND TAXPAYER AWARENESS ON TAXPAYER COMPLIANCE WITH TAXPAYER INTENTIONS AS AN INTERVENING VARIABLE - Nurhayati; Azhar Maksum; Narumodang B Siregar; Nasution, Fahmi Natigor (Riau International Conference on Economics, Business and Accounting, 2024)
This research aims to analyze the influence of tax morals, tax knowledge and tax awareness on taxpayer compliance with taxpayer behavioral intentions as an intervening variable inSmall and Medium Enterprise taxpayers registered in Rokan Hulu Regency. This research was conducted on Small and Medium Enterprise taxpayers registered in Rokan Hulu Regency. The data source is primary data obtained from distributing questionnaires. Sampling was taken using random sampling with a total of 104 respondents. The data analysis method uses the Structural Equation Modeling (SEM) model with the Partial Least Square (PLS) approach. The research results show that tax morale, tax knowledge and taxpayer awareness with taxpayer intentions as the intervening variable. These findings indicate that tax morale and taxpayer awareness influence taxpayer compliance, while tax knowledge does not influence taxpayer compliance. This research has limitations in that the tax knowledge variable has no effect on taxpayer compliance. So it is recommended that future researchers develop research by using the level of education and simplicity of the tax reporting system as variables that can be studied.